Age estimation of ancient skeletons based on the molar teeth attrition - Ramadhani, Triane Ayu; Sarilita, Erli; Malinda, Yuti; Yondri, Lutfi; Cunningham, Craig A; Oscandar, Fahmi (Odonto : Dental Journal, 2025)
Background: Two ancient skeletons (Subang Men) were excavated at the Subanglarang site, Subang Regency, West Java, Indonesia. The partial jaw containing set of teeth from the two skeletons was examined to determine the level of dental attrition present which was then used to estimate age at death.Objective: The aim of this study was therefore to determine the pattern of attrition on the molar teeth and use this to estimate the age at death of the Subang Men.Methods: The pattern of attrition in each cusp of the first molar (M1) and second molar (M2) was examined clinically and then compared with the Average Stage of Attrition (ASA) method. Estimated age was then estimated using formula that are outlined in the Average Stage of Attrition (ASA) method.Results: The results showed that the level of attrition that occurred in the M1 and M2 teeth of the two ancient man was significant. The estimated age at death calculated based on the attrition pattern of molar teeth for skeleton 1 was 38.9 and skeleton 2 was 61.9-64.6.Conclusion: Dental attrition which is caused by physiologic and pathologic teeth friction is related to age. Therefore, age estimation can be determined based on the attrition pattern that occurs in the teeth.